2008
DOI: 10.1080/03008200802148025
|View full text |Cite
|
Sign up to set email alerts
|

The Fras1/Frem Family of Extracellular Matrix Proteins: Structure, Function, and Association with Fraser Syndrome and the MouseblebPhenotype

Abstract: Fras1 and the structurally related proteins Frem1, Frem2, and Frem3, comprise a novel family of extracellular matrix proteins, which localize in a similar fashion underneath the lamina densa of epithelial basement membranes. They are involved in the structural adhesion of the skin epithelium to its underlying mesenchyme. Deficiency in the individual murine Fras1/Frem genes gives rise to the bleb phenotype, which is equivalent to the human hereditary disorder Fraser syndrome, characterized by cryptophthalmos (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 30 publications
1
34
1
5
Order By: Relevance
“…Fras1, Frem1, and Frem2 have been shown to form a physical complex that is essential for the basement membrane stabilization of each protein (Kiyozumi et al 2006). As such, null mouse models of each of these family members share a subset of phenotypes that includes subepidermal blebbing, cryptophthalmos, syndactyly, and renal dysgenesis (Petrou et al 2008). Individual mutants exhibit additional phenotypes that are also observed in Pdgfra-null embryos, such as craniofacial skeletal defects (Fras1, Frem1, and Frem2), hemorrhaging (Fras1 and Frem2), cardiac septal malformations (Frem2), abnormalities in neural tube development (Frem2), abnormal sternum and rib morphology (Fras1), and pigmentation defects (Frem2) Jadeja et al 2005;Timmer et al 2005;Slavotinek et al 2011;Vissers et al 2011;Miller et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Fras1, Frem1, and Frem2 have been shown to form a physical complex that is essential for the basement membrane stabilization of each protein (Kiyozumi et al 2006). As such, null mouse models of each of these family members share a subset of phenotypes that includes subepidermal blebbing, cryptophthalmos, syndactyly, and renal dysgenesis (Petrou et al 2008). Individual mutants exhibit additional phenotypes that are also observed in Pdgfra-null embryos, such as craniofacial skeletal defects (Fras1, Frem1, and Frem2), hemorrhaging (Fras1 and Frem2), cardiac septal malformations (Frem2), abnormalities in neural tube development (Frem2), abnormal sternum and rib morphology (Fras1), and pigmentation defects (Frem2) Jadeja et al 2005;Timmer et al 2005;Slavotinek et al 2011;Vissers et al 2011;Miller et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…By formation of a complex with FRAS1 and FREM2, FREM1 plays a role in dermal-epithermal adhesion prior to the expression of more permanent matrix proteins such as collagen during embryonic development. (2)(3)(4)(5)(6) Developmental consequences of FREM1 aberration include congenital disorders such as Manitoba-oculo-tricho-anal (MOTA) syndrome (MIM 248450) (7) and bifid nose, renal agenesis, and anorectic malformations (BNAR) syndrome (MIM 608980). (8) A splice variant of FREM1 has been found to influence cell survival and inflammation response.…”
Section: Introductionmentioning
confidence: 99%
“…It is encoded by the FRAS1 (Fraser syndrome 1) gene, of which mutations are observed to cause Fraser syndrome [15]. Recent studies revealed a functional cooperation between the FRAS1/Frem gene products, in which FRAS1, Frem1 and Frem2 are simultaneously stabilized at the lowermost region of the basement membrane by forming a macromolecular ternary complex [16].…”
Section: Discussionmentioning
confidence: 99%